Spatial Mapping and Determinants of Micro and Small Industry Concentration in Rural Areas of East Java Province - Rodhiah Umaroh; Listiono (East Java Economic Journal, 2026)
This study aims to analyze the spatial patterns and determining factors influencing the number of Micro and Small Industries (MSIs) in rural areas of East Java Province. Using 2024 PODES data from 3,225 rural villages, a spatial econometric approach is applied through Moran’s Index, Local Indicators of Spatial Association (LISA), as well as estimations of the Spatial Autoregressive (SAR) and Spatial Error Model (SEM). The results reveal significant positive spatial autocorrelation in the distribution of MSIs, with the identification of High-High clusters concentrated in several regencies such as Pamekasan, Sumenep, and Bojonegoro. Regression model estimations indicate that the number of village markets, the presence of public transportation, cooperatives, internet signal availability, access to microcredit, and social capital are positively associated with the number of MSIs. These findings underscore the importance of local infrastructure, digital access, economic institutions, and social networks in promoting rural microeconomic growth. The proposed policy implications include the development of MSI-based cluster areas, strengthening of connectivity infrastructure, and empowerment of village-level economic institutions with a spatial focus.